2007
DOI: 10.1007/s10805-007-9046-4
|View full text |Cite
|
Sign up to set email alerts
|

Business Faculty Perceptions and Actions Regarding Ethics Education

Abstract: This paper examines faculty perceptions regarding ethical behavior among colleagues and students, and faculty practices with regard to teaching ethics in three institutions over a 4-year period. Faculty reported an uneven pattern of unethical behavior among colleagues over the period. A majority of business courses included ethics, however as both a specific topic on the syllabus and within course discussions. The percentage of courses with ethics discussions increased in 2006, however, the time allocated to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Implicitly, all values have a heavy ethical content and are based upon how individuals frame the duties that they owe to others with whom they hold a unique relationship, to self, to a higher power, or to society (Caldwell and Hayes, 2007). The teaching of business ethics has been addressed by a variety of studies (Bean and Bernardi, 2007;Beauvais et al, 2007;Gonin, 2007;Poff, 2007), with scholars (Boyle, 2007) and practitioners (Krehmeyer, 2007) debating the most effective approach to influencing behaviors about moral conduct. Penn and Collier (1985) advocated the teaching of moral reasoning more than 20 years ago and recommended that this teaching utilized Kohlberg's moral reasoning model.…”
Section: Creating a Culture Of Integritymentioning
confidence: 99%
“…Implicitly, all values have a heavy ethical content and are based upon how individuals frame the duties that they owe to others with whom they hold a unique relationship, to self, to a higher power, or to society (Caldwell and Hayes, 2007). The teaching of business ethics has been addressed by a variety of studies (Bean and Bernardi, 2007;Beauvais et al, 2007;Gonin, 2007;Poff, 2007), with scholars (Boyle, 2007) and practitioners (Krehmeyer, 2007) debating the most effective approach to influencing behaviors about moral conduct. Penn and Collier (1985) advocated the teaching of moral reasoning more than 20 years ago and recommended that this teaching utilized Kohlberg's moral reasoning model.…”
Section: Creating a Culture Of Integritymentioning
confidence: 99%
“…In contrast, Klein argued that business professors are not able to teach ethics about their disciplinary and claimed that only philosophers are qualified to do so. 20 Although academic members look positively to mention ethics in their classes, their knowledge about ethical issues has to be investigated. More than half of academic members reported that ethical discussions were organized rarely in their faculty.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…In comparison with most other social sciences fields, there is a substantial research base covering integrity and misconduct in economics and business subjects, perhaps as a result of the corporate collapses attributed to unethical behavior (O'Leary and Cotter 2000; Smyth and Davis 2004;Beauvais et al 2007;Mirshekary et al 2010). Concerns have been expressed over business schools teaching students to be successful without placing sufficient emphasis on moral responsibilities (Stevens et al 1993).…”
Section: Economics and Business Studiesmentioning
confidence: 99%
“…The incorporation of ethics into curricula and subject matter content may in fact lead to the faculty spending less time on ethics than it would if ethics were dealt with through a single course or separate ethics courses (Beauvais et al 2007). This evidence suggests that it is important for the faculty to consider how ethics and integrity contents fit in with the overall program and course objectives and at what points in the curriculum this content is best addressed and why.…”
Section: Integrated Ethics and Integrity Contentmentioning
confidence: 99%
See 1 more Smart Citation